The Impact of Spin-Off Policy To The Profitability On Indonesian Islamic Banking Industry - Abdul Hamid (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2015)
The purpose of this paper is to analyze that the spinoff policy that based on Islamic Banking Act No. 21/2008 had an impact on the profitability  ratio  of  Islamic  banking  industry  in  Indonesia.  This  research  used ordinary least square regression. The variable used in this paper is spin-off which is used as a dummy variable, and also included the internal factor of industry such  as  deposit  margin,  non-performing  financing  (NPF),  and  efficiency  ratio (measured by BOPO). The result showed that dummy variable of spin-off, NPF and BOPO had an impact on the profitability in Indonesian Islamic banking industry. The implication of this result is spin-off policy had a good impact on the profitability in Indonesian Islamic banking industry. According to this result, Bank Indonesia should stimulate the Islamic banking unit to spin-off from their parents conventional banks.DOI:10.15408/aiq.v7i1.1363